Environmentally friendly approach for sustainable recycling of spent SCR catalysts and Al alloy scrap to prepare TiAl3 and low-Fe Al alloys. Issue 16 (1st August 2022) - Zhang, Yakun; Lei, Yun; Ma, Wenhui; Ren, Yongsheng; Chen, Qiushi; Huan, Zhaoyang
Abstract : A new environmentally friendly (no waste gas, liquid, and slag), efficient (two steps), and low-cost (wastes as raw material) approach is proposed to recycle spent SCR catalysts and Al alloy scrap for preparing TiAl3 and low-Fe Al alloys. Abstract : With the rapid reduction in NO x emissions and the end of various Al alloy products' lives in recent years, large amounts of spent SCR catalysts (SSCs) and Al alloy scrap (AAS) as important secondary Ti and Al resources have been discarded. The value-added reutilization of Ti and Al from the two wastes is necessary to develop sustainable Ti and Al resources. In this work, an environmentally friendly approach is proposed to simultaneously recycle Ti and Al from the two wastes and then prepare them into TiAl3 and low-Fe Al alloys. First, AAS (1.25 wt% Fe) was used as a reductant to extract Ti and W from the SSC to prepare raw W-containing Ti–Al alloys. The results showed that applying a MgO crucible and electromagnetic force can promote alloy–slag separation and a MgO crucible increased the extraction ratio of Ti and W. Next, the raw Ti–Al melt was separated by electromagnetic directional crystallization for the simultaneous preparation of the two high-value products: W-containing TiAl3 and low-Fe Al (0.41 wt% Fe) alloys. In the separation process, Ca, Mg, and Zn impurities in the alloys were removed via volatilization; Fe and Mn impurities were eliminated through agglomeration at the boundary between the TiAl3 and low-Fe Al alloys and at the top of the Ti–Al alloy. The entire process produces no waste liquid, gas, or slag. This method provides new environmentally friendly insights for sustainable recycling of secondary Ti and Al resources, and provides a new technology for preparing TiAl3 and low-Fe Al alloys.